Pumped thermal energy storage with heat pump-ORC-systems: Comparison of latent and sensible thermal storages for various fluids - Eppinger, Bernd; Zigan, Lars; Karl, Jürgen; Will, Stefan (Applied Energy, 2020)
To compensate for the recurring daily fluctuations of the power generation of renewable energies, energy storage systems are necessary that are able to adjust the time shift of the power generation to the required load profiles with high numbers of cycles and high capacity. Due to their independence from geographical and geological requirements, Pumped Thermal Energy Storages (PTES) are a possible form of energy storage in system-relevant orders of magnitude for these requirements. Compared to electric resistance heaters, the round trip efficiency can be significantly improved by using a heat pump in the PTES. A further improvement occurs when low-temperature waste heat from other processes or sources (such as solar or geothermal energy) is used for the heat pump. The use of most components of the heat pump for an Organic Rankine Cycle (ORC) for heat to power conversion drastically increases the cost efficiency of the storage concept, but requires both cycles to run on the same fluid. The goal of this work is to identify optimal fluids and operating parameters for the combined cycle. Both latent and sensible storage systems are considered for different fluids and are examined for their suitability for different operating conditions with a focus on the behaviour of cyclopentane, R1233zd(E), Novec 649 and R365mfc. The fluids and storage systems are evaluated by defining a reference case and by varying different parameters of this reference case. The simulations were performed using a custom Matlab® model and fluid data provided by REFPROP. With general conditions for small applications in the size of a demonstration plant with 20 kW electrical input power, power to power (ηP2P" role="presentation">) efficiencies of over 80% are demonstrated. With simple sensible storage media, ηP2P" role="presentation"> efficiencies of 62% are achieve
Keywords: Fluid variation; Heat pump (HP); Pumped thermal energy storage (PTES); Sensible; Latent; Organic Rankine Cycle (ORC)